2007
DOI: 10.1007/s12032-007-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell invasion and MMP production by a nutrient mixture in malignant liposarcoma cell line SW-872

Abstract: Liposarcoma, a malignancy of fat cells, is the most common soft tissue sarcoma. Though rare, poorly differentiated liposarcomas commonly metastasize to lungs and liver, leading to poor prognosis. Prevention of Extracellular matrix (ECM) degradation by inhibition of matrix metalloproteinases (MMPs) activity has been shown to be a promising therapeutic approach to inhibition of cancer progression. A nutrient mixture (NM) containing lysine, proline, ascorbic acid, and green tea extract has shown significant antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…MMP-2 and -9 are soluble MMPs which degrade gelatine and play key roles in tumor angiogenesis, growth and metastasis [11]. Several studies have demonstrated their role in sarcoma progression [7], [39][42]. Our results have shown that MMP-2 and -9 were significantly increased in costunolide-treated SW-982 and TE-671 and dehydrocostus-lactone-treated TE-671 cells.…”
Section: Discussionsupporting
confidence: 53%
“…MMP-2 and -9 are soluble MMPs which degrade gelatine and play key roles in tumor angiogenesis, growth and metastasis [11]. Several studies have demonstrated their role in sarcoma progression [7], [39][42]. Our results have shown that MMP-2 and -9 were significantly increased in costunolide-treated SW-982 and TE-671 and dehydrocostus-lactone-treated TE-671 cells.…”
Section: Discussionsupporting
confidence: 53%
“…The proteins are known to play a role in the proliferation and migration of normal stem cells and tumor cells (4) and in liposarcoma progression (5). One of the functions of ECM in regulating cell behavior is through their receptors on the cell surface called heterodimer integrins, which consist of a and b subunits (6).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained with in vitro cancer models in which 1000 μg/ml NM resulted in growth inhibition of various cancer cell lines as seen in Table 2. The breast cancer cell line MDA-MB-231 [35] showed a growth inhibition of 50%, while melanoma A2058 [36] and liposarcoma SW-872 [37] showed inhibition of 64% and 61%, respectively. A relatively lower growth inhibition was seen in the osteosarcoma cell line MNNG which showed an inhibition of only 10% [38].…”
Section: Discussionmentioning
confidence: 98%